Tareas escolares y el aprendizaje significativo en la Unidad Educativa Jorge Icaza parroquia Eloy Alfaro del cantón Latacunga en el año lectivo 2019 - 2020. - Rodríguez Velasteguí, Ana Gabriela (2021)
The research project addressed the problem of the limited interest of students in the development of school tasks, as well as repetitive strategies and activities carried out by the teachers. With the aim of designing methodological strategies to enhance meaningful learning through homework at the Jorge Icaza Educational Unit; Its elaboration will be of great contribution by the innovation, interaction and motivation for the student. The research was developed with a qualitative and quantitative approach, since an observation sheet was applied in class to teachers in the fourth year of elementary education, through this it was possible to know that there is disinterest on the part of the student in developing the tasks, causing Ignorance of the subject, a significant deficient learning and therefore problems in their academic performance by not understanding how to carry out their activities. Based on the results, the proposed "Methodological guide to enhance meaningful learning through school tasks" is designed, which consists of didactic strategies such as illustrations, role play, philosophical chairs, COPISI method and problem-based learning. These techniques are framed in the themes of the basic general education curriculum and focused on the subjects of mathematics, social sciences, natural sciences, language and literature, this proposal was validated by experts who mentioned that it is an important contribution to education. Regarding the conclusions, it was determined that the student's disinterest was originated by the same technique used in the performance of school tasks, memorization, copying, aspects that demotivate the student.